2016
DOI: 10.1148/radiol.2015141922
|View full text |Cite|
|
Sign up to set email alerts
|

Myeloperoxidase Nuclear Imaging for Epileptogenesis

Abstract: q RSNA, 2015 Purpose:To determine if myeloperoxidase (MPO) is involved in epileptogenesis and if molecular nuclear imaging can be used to noninvasively map inflammatory changes in epileptogenesis. Materials and Methods:The animal and human studies were approved by the institutional review boards. Pilocarpine-induced epileptic mice were treated with 4-aminobenzoic acid hydrazide (n = 46), a specific irreversible MPO inhibitor, or saline (n = 42). Indium-111-bis-5-hydroxytryptamide-diethylenetriaminepentaacetate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 34 publications
1
19
0
Order By: Relevance
“…We show an increase in MPO activity in positive control animals, as reported previously [56]. However, treatment with zingerone alleviated MPO content, indicating the anti-inflammatory role of zingerone, as reported [57].…”
Section: Discussionsupporting
confidence: 90%
“…We show an increase in MPO activity in positive control animals, as reported previously [56]. However, treatment with zingerone alleviated MPO content, indicating the anti-inflammatory role of zingerone, as reported [57].…”
Section: Discussionsupporting
confidence: 90%
“…SPECT/CT imaging confirmed that MPO activity was inhibited. Also, MPO was present in the temporal lobe of an epileptic patient, which was absent in controls [ 149 ]. Studies on the role of MPO in brain injury are essential, but so is the specific type of injury.…”
Section: Mpo Usefulness As a Biomarker In Disease Statesmentioning
confidence: 99%
“…Superoxide generates hydrogen peroxide (H 2 O 2 ), a substrate of myeloperoxidase (MPO), an enzyme found in phagocytes and mainly in neutrophils (Hernandes and Britto 2012). NOX2derived reactive oxygen species (ROS) and MPO are suggested to be involved in a variety of processes of epileptogenesis and constitute an extremely deleterious event considered to be a cause and consequence of prolonged seizures (Zhang et al 2016).…”
Section: Introductionmentioning
confidence: 99%